ANALISIS YURIDIS PEMBERANTASAN TINDAK PIDANA TERHADAP PELAKU PENYALAHGUNAAN NARKOBA (STUDI PENELITIAN DI BNNP KEPULAUAN RIAU) - Putri Natasya; Siti Nur Khotijah; Kaspol Jihad (Ensiklopedia of Journal, 2022)
In accordance with Law No. 35 of 2009 concerning Narcotics has regulated the types and sanctions given to narcotics crimes, among others: Criminal acts for abusers or as victims of narcotics abuse, the abuser is obliged to undergo medical rehabilitation and social rehabilitation, Criminal Acts of Parents/Guardians from Narcotics addicts who are not yet old enough (Article 128) shall be sentenced to a maximum imprisonment of 6 (six) months or a maximum fine of Rp. 1,000,000.00 (one million rupiah). This research uses library research method or library research. The data sources used are primary and secondary data from press releases, as well as data from the Sub-Directorate of Drugs of the Ditreskrimkhus of the Riau Islands Police, the data will be analyzed using descriptive analysis methods. The theoretical basis used is interviews. In principle, the scope of criminal law includes three provisions, namely criminal acts, liability, and punishment. The criminal provisions contained in Law No. 35 of 2009 concerning Narcotics is formulated in Chapter XV of Criminal Provisions Articles 111 to 148. Law no. 35 of 2009 concerning Narcotics, there are four categorizations of unlawful acts that are prohibited by law and can be threatened with criminal sanctions. The National Narcotics Agency of Riau Islands Province in uncovering criminal cases of Narcotics Abuse, has a role in conducting investigations related to reports from the public, the Riau Islands BNNP also makes various efforts to reduce the occurrence of criminal acts of Narcotics Abuse in Riau Islands such as penal and non-penal efforts in tackling criminal acts. Narcotics Abuse in Riau Islands.Keywords: Eradication, Criminal Perpetrators, Narcotics Abuse